KAJIAN PEMBERDAYAAN UMKM KOTA MAKASSAR SEBAGAI UPAYA PENINGKATAN KESEJAHTERAAN PELAKU USAHA - Arsad Bahri; Usman Mulbar; Andi Suliana (Jurnal Inovasi dan Pelayanan Publik Makassar, 2019)
Micro, Small and Medium Enterprises (MSMEs) are one of the main pillars of the national economy with an independent perspective having great potential to improve welfare. This study aims to determine the form of empowerment that is carried out to MSMEs as an effort to improve the welfare of business owner in Makassar City, as well as to determine the response of business owners related to the empowerment program that has been carried out by the local government, especially through the Cooperatives and MSMEs Service in Makassar. The population in this study are all business owners in Makassar, both those who have participated in empowerment programs from the government and those who have never participated in these programs. The sample in this study was 60 business people selected by purposive sampling by considering several criteria both from the type of business and the background of the business owner so that respondents in this study could be heterogeneous. In addition, interviews were conducted with academics. Research instruments in the form of questionnaires and interview guidelines. Data were analyzed descriptively qualitatively. The results showed that: 1) Empowerment programs desired by business owners tended to lead to improvements in the quality of business products and empowerment programs focused on product marketing training. 2) Recommendations related to the results of research, namely: a) Every empowerment program to be carried out by the government should be prepared based on an analysis of the needs of the beneficiaries in this case business owners. b) Empowerment programs carried out by the government should be directed at improving the quality of business products and training in marketing products or providing containers to business people to market their business products. c) The program held should be able to socialize well and evenly to all business owners. This can be achieved when every information from the government is easily accessed by all business owners.